1996
DOI: 10.1083/jcb.135.5.1369
|View full text |Cite
|
Sign up to set email alerts
|

Presence of double-strand breaks with single-base 3' overhangs in cells undergoing apoptosis but not necrosis.

Abstract: Abstract. Apoptotic cells in rat thymus were labeled in situ in paraffin-embedded and frozen tissue sections by ligation of double-stranded DNA fragments containing digoxigenin or Texas red. Two forms of doublestranded DNA fragments were prepared using the polymerase chain reaction: one was synthesized using

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
162
0
2

Year Published

1998
1998
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(168 citation statements)
references
References 32 publications
4
162
0
2
Order By: Relevance
“…The presence of some such 3' -recessed ends in gluco corticoid-treated thymic lymphocytes had previously been deduced by labeling with the Klenow fragment of DNA polymerase (Peitsch et aI., 1993). However, a com pletely opposite conclusion was reached in another re cent study, in which it was suggested that the majority of fragment ends in thymus have single-base 3' overhangs, although some blunt-ended fragments were also present (Didenko and Hornsby, 1996). The methods used to gen erate these latter findings are not quantitative, so the LM-PCR method appears to produce the most reliable information owing to its semiquantitative nature.…”
Section: Klenow Polymerase Treatment (A)mentioning
confidence: 95%
“…The presence of some such 3' -recessed ends in gluco corticoid-treated thymic lymphocytes had previously been deduced by labeling with the Klenow fragment of DNA polymerase (Peitsch et aI., 1993). However, a com pletely opposite conclusion was reached in another re cent study, in which it was suggested that the majority of fragment ends in thymus have single-base 3' overhangs, although some blunt-ended fragments were also present (Didenko and Hornsby, 1996). The methods used to gen erate these latter findings are not quantitative, so the LM-PCR method appears to produce the most reliable information owing to its semiquantitative nature.…”
Section: Klenow Polymerase Treatment (A)mentioning
confidence: 95%
“…Doublestranded DNA is subject to the activity of endonucleases, which can induce cuts with staggered ends and blunt ends. 16 The characteristic pattern of apoptosis is double-stranded breaks at internucleosomal DNA sites such that the breaks have staggered ends with 3Ј overhangs comprising 1 or 2 bases, or longer overhangs involving 4 bases. 16 A histochemical method using Taq polymerase detects single-base 3Ј overhangs produced by Ca 2ϩ -dependent DNAase I, whereas the method using TdT detects 1-base 3Ј overhangs as well as multiple-base 3Ј overhangs produced by pH-dependent DNAase II and possibly other DNAases.…”
Section: See P 1422mentioning
confidence: 99%
“…16 The characteristic pattern of apoptosis is double-stranded breaks at internucleosomal DNA sites such that the breaks have staggered ends with 3Ј overhangs comprising 1 or 2 bases, or longer overhangs involving 4 bases. 16 A histochemical method using Taq polymerase detects single-base 3Ј overhangs produced by Ca 2ϩ -dependent DNAase I, whereas the method using TdT detects 1-base 3Ј overhangs as well as multiple-base 3Ј overhangs produced by pH-dependent DNAase II and possibly other DNAases. 16 Although the TdT-based TUNEL assay is less specific, comparable results of the Taq polymerase-based in situ ligation and TdT-based TUNEL methods have been reported in a recent study.…”
Section: See P 1422mentioning
confidence: 99%
See 1 more Smart Citation
“…De todas ellas, la más importante es la que se refiere a las alteraciones del ADN. En todo proceso de muerte celular se produce la activación de unas enzimas, las nucleasas, que fragmentan al ADN 3 . Mientras que en la apoptosis se activan selectivamente ciertas endonucleasas que fragmentan al ADN sólo en sitios internucleosomales, en la oncosis se activan más generalizadamente endonucleasas y exonucleasas, que fragmentan al ADN tanto en sitios internucleosomales como nucleosomales.…”
Section: Apoptosis In Cardiovascular Diseasesunclassified